Sosialisasi Uji Emisi Kendaraan di Desa Panggung Kabupaten Tanah Laut - Yunus, Muhammad; Bayu Agung Wicaksono; Sri Muntiah Andriami; Taufik Abdullah Attamimi (Apik Cahaya Ilmu, 2025)
The vehicle emission testing awareness programme in Panggung Village, Pelaihari Subdistrict, Tanah Laut Regency aims to raise public awareness of the importance of vehicle emission testing in controlling air pollution. Using a qualitative and participatory approach, this activity involves planning, material preparation, practical demonstrations, and ongoing assistance. Program results show a significant increase in community understanding of vehicle emissions testing and its impact on health and the environment. 85% of participants reported feeling more aware of the importance of emissions testing, and 60% began regularly conducting emissions testing on their vehicles. Practical demonstrations using Arduino-based tools and gas sensors successfully improved community skills in conducting emissions testing. Ongoing support ensures sustainable implementation. This programme provides an effective model for increasing community participation in air pollution control in rural areas and can be applied in other villages facing similar challenges.